Learn C on the Mac - Mark, David (Apress : Imprint: Apress, 2009)
Considered a classic by an entire generation of Mac programmers, this popular guide has been updated for Mac OS X. Don't know anything about programming? No problem! Acclaimed author Dave Mark starts out with the basics and takes you through a complete course in programming C using Apple's free Xcode tools. This book is perfect for beginners learning to program. It includes Mac OS X examples! Provides best practices for programming newbies Written by the expert on C-programming for the Mac Presents all the basics with a pragmatic, Mac OS X-flavored approach Includes updated source code which is fully compatible with Xcode 4.